Diagnosing Organizational Effectiveness in PT MIT Using 7S MCKINSEY and CUSTOMER PERSPECTIVE (The Indonesian Journal of Business Administration, 2014)
Abstract - For 20 years of its existence, PT MIT’s growth rate is slow. From the past five periods, the company’s net income in 2012 have the biggest decline which about 79% from the previous year. There are some issues that makes the company facing a slow growth rate. Two main aspects are financial area and managerial area. The main problem faced by PT MIT is the target of the company during the previous years until 2012 is not achieved, not only the punctuality of the project’s completion but also the revenue, this lead to financial crisis and poor customer satisfaction. These can be a threat to the achievement of organization performance. Based on analyzing internal condition conducted using 7S McKinsey framework, this analyzing revealed from 7 elements of organization which are Strategy, Structure, Systems, Staff, Skill, and Shared Values, there are shortcomings in Structure, System, Shared Values, and Style. This research obtain primary data through survey method by using questionnaire and secondary data by taking interview and literature documents. This study analyzed the outcome of the organizational element using customer satisfaction survey, from nine factors measurement which are Service, Accuracy, Inspectors’ Skills, Hospitality, Ease of Communication, Quality of Reports, Inspectors’ Cooperation, Adequate Equipment, and Price, there is Accuracy factor regarding the timeliness completion of projects that got less satisfaction and being a concern for the company to develop. This research provides strategy for PT MIT in order to improve corporate performance by implementing the recommendation that supported by ADKAR change management. Keywords: organization effectiveness, organizational performance, 7S McKinsey framework, ADKAR change management